PENGARUH TINGKAT MARGIN KEUNTUNGAN, PRODUK DOMESTIK BRUTO DAN INFLASI TERHADAP PERMINTAAN PEMBIAYAAN MURABAHAH PADA BANK BRI SYARIAH TAHUN 2010-2019 - Meiliza Shelly; Mayes Anthony; Richard Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to determine the Effect of Profit Margin Rate, Gross Domestic Product and Inflation to Murabahah Financing Demand at BRI Syariah in 2010-2019. This research uses secondary data obtained from the financial statement published, that is official website Bank BRI Syariah, Bank Indonesia and Central Agency of Statistic from 2010 to 2019 time span. In this research using Ordinary Least Square (OLS) method to determine the change of value of the dependent variable that is murabahah financing (Y) influenced by independent variable that is profit Margin Rate (X1), gross domestic product (X2) and inflation (X3) by using multiple linear regression technique. The method used in this research is quantitative descriptive, which is to explain the results of computerized with using E-Views program 10 version. The results showed that the simultaneous test (Test F) produces a calculated F value of 121.8721 with a probability (F-statistic) of 0.000000 thus the probability (F-statistic) is smaller than alpha (0.000000<0.05) which means H0 rejected and Ha accepted. This means that the profit of margin, GDP and inflation simultaneously have a significant on the demand for murabahah financing at BRI Syariah banks in the period 2010-2019. Partial regression test (t test) shows that the level of margin has a positive and significant on the demand for murabahah financing, GDP has a positive and significant on the demand for murabahah financing, while inflation has no significant on the demand for murabahah financing at BRI Syariah Bank. he results of the coefficient of determination (R2) of the independent variables on the dependent variable obtained a value of 0.975781. This means that the contribution of the influence of the independent variable (margin level, GDP and inflation) to the dependent variable (murabaha financing demand) is 97,58% and the remaining 2,42% is influenced by other variables outside the regression model in this study.Keywords : The Profit Margin, GDP, Inflation, Murabahah Financing